Pengaruh Citra Merek dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Honda pada UD Sonic Motor Kecamatan Kampar - Rosadi, Ikhsan; Mardiah, Ainun; Sehani, Sehani (Policy, Law and Political Research Center, 2023)
The purchasing decision is the final stage in the decision-making process where consumers actually make a purchase. Before making a purchase, consumers go through several stages in the buying process. The research aims to determine the extent of the influence of brand image and promotion on the purchasing decision of motorcycles. The research results show that the brand image variable (X1) has a calculated t-value of (2.471) > t-table (1.985), thus it can be concluded that the brand image variable partially has a positive influence on the purchasing decision. The promotion variable (X2) shows a calculated t-value of (3.235) > t-table (1.985), thus it can be concluded that the promotion variable partially has a positive influence on the purchasing decision. Therefore, it can be inferred that there is a significant influence between brand image and promotion simultaneously on the purchasing decision of Honda motorcycles.